Kidney disease in hospitalised HIV positive children in Ibadan, South West Nigeria (2012)
Background: There is a paucity of data on the clinicopathologic pattern of kidney disease in Human Immunodeficiency Virus (HIV) seropositive children from sub-Saharan Africa and non from South West Nigeria. Objective: To determine the clinical pattern and outcome of kidney disease among HIV positive children hospitalised at a tertiary hospital South West Nigeria Methodology: A retrospective study of all HIV positive children who were hospitalised and managed for kidney diseases over a period of 78 months at the University College Hospital Ibadan, South West Nigeria was reviewed. Patients were followed up over the duration of hospital admission. Results: Ten children (six males and four females) aged 4 -15(10.4±3.2) years were identified. Four presented in acute kidney injury, (AKI) three with nephrotic syndrome (NS) and two in chronic kidney failure (CKF). One patient had left renal artery stenosis. Renal biopsy performed in three children showed focal segmental glomerulosclerosis in two patients and membranous nephropathy in the third. Management included antiretroviral therapy, Angiotensin Converting Enzyme Inhibitors and acute haemodialysis. Mortality was 40%. Conclusion: AKI, NS and CKF were the predominant clinical patterns of kidney disease in hospitalised HIV positive children and the mortality is high